Chemical change during storage of crambe cultivated with application of plant growth regulators (Bioscience Journal, 2020)
This study aimed to characterize the chemical composition of crambe grains produced with plant growth regulators in the 2014 and 2015 harvests and stored for 180 days. During crambe cultivation, two foliar sprayings were carried out with the following treatments: 1) control treatment with distilled water; 2) indole-3-acetic acid 100 mg L-1 (IAA); 3) 3-gibberellic acid P.A. 100 mg L-1 (GA3); 4) Stimulate®. After harvesting, the grains were analyzed initially and after 180 days of uncontrolled storage. We checked water content, lipids in hot extraction (HE), lipids in cold extraction (CE), proteins, acidity and antioxidant activity. The Tukey test was used to compare the averages (p